Towards enhancement of fungal hydrolytic enzyme cocktail using waste algal biomass of Oscillatoria obscura and enzyme stability investigation under the influence of iron oxide nanoparticles - Khan S.; Khan M.; Ahmad S.; Sherwani S.; Haque S.; Bhagwath S.S.; Kushwaha D.; Pal D.B.; Mishra P.K.; Srivastava N.; Gupta V.K. (My University, 2025)
Development of low-cost and economic cellulase production is among the key challenges due to its broad industrial applications. One of the main topics of research pertaining to sustainable biomass waste based biorefinaries is the development of economic cellulase production strategies. The main cause of the increase in cellulase production costs is the use of commercial substrates; as a result, the cost of any cellulase-based bioprocess can be decreased by employing a productive, low-cost substrate. The goal of the current study is to develop low-cost cellulase using the carbohydrate-rich, renewable, and widely accessible cyanobacteria algae Oscillatoria obscura as the production substrate. Maximum cellulase was produced utilising the fungus Rhizopus oryzae at substrate concentration of 7.0 g among various tested concentrations of algal biomass. Maximum production rates of 22 IU/gds FP, 105 IU/gds BGL, and 116 IU/gds EG in 72 h were possible under optimal conditions and substrate concentration. Further investigations on the crude enzyme's stability in the presence of iron oxide nanoparticles (IONPs) revealed that it was thermally stable at 60 °C for up to 8 h. Additionally, the crude enzyme demonstrated pH stability by maintaining its complete activity at pH 6.0 for 8 h in the presence of the optimal dose of 15 mg IONPs. The outcomes of this research may be used to investigate the possibility of producing such enzymes in large quantities at low cost for industrial use. © 2022 Elsevier B.V.